Methodology for the development of physical qualities in track-and-field runners at the stage of sports mastery improvement - Sorokin, D.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is the theoretical substantiation of a comprehensive methodology for the directed development of the speed-strength abilities, special endurance, strength, and flexibility of qualified runners within the framework of the annual cycle. Methods and structure of the study. The methodology includes the analysis of scientific-methodological literature, the systematisation of approaches to the periodisation of loads, and the identification of optimal means of developing the leading qualities. Results and conclusions. The analysis of the sources showed that in highly qualified athletes the limiting factors are special endurance and running economy. The main approaches rely on the principles of wave-like periodisation. The methodology is built on the integration of the means of running preparation, speed-strength exercises, plyometrics, and gymnastic complexes. The theoretical generalisation made it possible to determine a rational distribution of loads: the predominance of aerobic work in the preparatory period with a gradual increase of the share of high-intensity means in the pre-competition cycle. Attention is paid to the individualisation of the impacts taking into account the morphofunctional features of the athletes and to the control over the recovery of the body. The mechanisms of adaptation to combined loads and the influence of strength preparation on the power of push-off are considered.